Airline Efficiency in Asia Following Liberalization of International Air Transport - Muhammad Asraf, Abdullah; Mohd Satar, Nurulhuda; H Peoples, James (Nova Science Publishers, 2020)
Governments in the Asia Pacific region have introduced policies that increasingly enhance the role of market forces in the international airline industry. While theory suggests liberalization of airline operations should promote greater efficiency in this industry, this study observes challenges from stepped-up global competition has actually created a business environment that contributes to production inefficiencies. We use the stochastic frontier approach to estimate technical, allocative and cost inefficiencies for airline companies from 17 countries in the Asia Pacific region. Findings support this study’s observation on liberalization and production efficiency, as estimates show declining technical efficiency over the 9-year observation period. In addition, findings on non-labor inputs reveal at the mean these companies tend to under-utilize fuel and aircrafts. In contrast, companies in the ASEAN region slightly under-utilize workers, while companies in non-ASEAN countries over-utilize workers. We argue these findings do not support abandonment of liberalization policies, but rather reveal the importance of airline companies in this region adjusting to a more competitive global market.